Simulation of ground water quality for noyyal river basin of Coimbatore city, Tamilnadu using MODFLOW. (November 2022) - Lenin Sundar, M.; Ragunath, S.; Hemalatha, J.; Vivek, S.; Mohanraj, M.; Sampathkumar, V.; Mohammed Siraj Ansari, A.; Parthiban, V.; Manoj, S.
Abstract: In recent years groundwater modelling has become a major part of many projects dealing with groundwater exploitation, protection and remediation. Coimbatore city is located along the Noyyal River which is grown in size and population on either side of the river and the dumping of wastes very close to the river banks, leads to pollution of both surface and groundwater. Study on the quality of groundwater along the Noyyal River in Coimbatore city of Tamilnadu, is necessary to safeguard the interest of the people with respect to quality and quantity of water. The objective of the research is to develop Groundwater quality models to suggest ways and means to contain and remediate the polluted groundwater under various conditions. Data related to the groundwater quality, rainfall and well log were collected from the reputed government departments and fifteen sample well locations are identified near the noyyal river basin. The quality parameters such as pH, TDS, EC, TH, chlorides, alkalinity, sodium, calcium, magnesium, sulphates and nitrates are considered for the study. Groundwater quality modelling is attempted by using MODFLOW/MT3DMS with different scenarios. This study revealed that in all the scenarios the center portion of study area is more affected i.e. from P·N.Palayam to Kalangal. The groundwater flow is moving towards and along the river flow. Hence the pollutants are moving easily from upstream to the downstream side. necessary measures has to be taken to control the groundwater contamination. Graphical abstract: Image 1 Highlights: To determine the physico-Chemical Characterization of the ground water samples to understand its nature. To identify the groundwater vulnerable zones in the study area. To predict the vulnerability validity in a futuristic manner. To suggest a suitable remedial measures for the ground water contamination.